Correlation between Adherence and Effectiveness of Tuberculosis Medication Use among Patients - Zuniarto, Ahmad Azrul; TW, Siti Pandanwangi; Annisa, Fatin Maura (Newinera Publisher, 2024)
Indonesia has become the country with the second highest number of tuberculosis cases in the world. In 2021, Indonesia recorded an incidence of 397,377 cases, with a significant number of cases originating from Tegal, Central Java, which reported 980 cases. The purpose of this study is to determine the compliance and effectiveness of TB medication usage and to examine the relationship between compliance, effectiveness, and patient sociodemographics. The study population consists of tuberculosis patients at the Tegal Selatan Community Health Center who underwent treatment from September 2023 to February 2024. The research method is quantitative causal. Data collection was conducted both retrospectively and prospectively. Compliance data were obtained through the MMAS-8 questionnaire, and effectiveness data were gathered by recording follow-up sputum examinations using the SITB (Tuberculosis Information System) software. The study included 30 respondents, with 50% male and 50% female. The majority (63.3%) were middle-aged adults (41-60 years old), 63.3% had less than 9 years of education, 60% were employed, 93.3% had an income at or below the minimum city wage, and 70% had 1-3 family dependents. 76.7% of respondents exhibited high compliance, 20% had moderate compliance, and 3.3% had low compliance. The effectiveness of medication usage was 96.7%. Chi-square analysis (95% CI) revealed a strong correlation between compliance and effectiveness with r = 0.707 (p-value = 0.033), and there was no significant relationship between patient sociodemographics and both compliance and effectiveness.